Hygge: Rahasia Hidup Bahagia Orang Denmark - Frendi Krisman Gulo (Yayasan Aya Sophia Indonesia, 2023)
The purpose of this study is to find out a brief study of the thoughts from the Youtube channel M Channel entitled